18.7k views
3 votes
onsider the binomial distribution with n trials and P(S) = p. (a) Show that p(y) p(y − 1) = (n − y + 1)p yq for y = 1, 2, , n. Equivalently, for y = 1, 2, , n, the equation p(y) = (n − y + 1) p yq p(y − 1) gives a recursive relationship between the probabilities associated with successive values of Y.

1 Answer

2 votes

Answer:

explanation is attached below

Explanation:

onsider the binomial distribution with n trials and P(S) = p. (a) Show that p(y) p-example-1
User Lundstromski
by
6.0k points